2022
DOI: 10.1093/bjs/znac109
|View full text |Cite
|
Sign up to set email alerts
|

Delays to revascularization for patients with chronic limb-threatening ischaemia

Abstract: Background Vascular services in England are organized into regional hub-and-spoke models, with hubs performing arterial surgery. This study examined time to revascularization for chronic limb-threatening ischaemia (CLTI) within and across different care pathways, and its association with postrevascularization outcomes. Methods Three inpatient and four outpatient care pathways were identified for patients with CLTI undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…To overcome the lack of specific diagnostic codes for CLTI, studies using HES data to evaluate outcomes after revascularisation procedures have used a combination of the urgency of admission variable and codes relating to PAD overall or signs of the disease, such as ulcers and gangrene, as a proxy for the severity of the disease in risk-adjustment models. 3 Our study found that using the emergency mode of admission and ICD-10 codes corresponding to PAD had high specificity but low sensitivity of diagnosing chronic limb-threatening ischaemia. This approach has two important limitations.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…To overcome the lack of specific diagnostic codes for CLTI, studies using HES data to evaluate outcomes after revascularisation procedures have used a combination of the urgency of admission variable and codes relating to PAD overall or signs of the disease, such as ulcers and gangrene, as a proxy for the severity of the disease in risk-adjustment models. 3 Our study found that using the emergency mode of admission and ICD-10 codes corresponding to PAD had high specificity but low sensitivity of diagnosing chronic limb-threatening ischaemia. This approach has two important limitations.…”
Section: Discussionmentioning
confidence: 60%
“…Data about the care received by patients with PAD are available within the Hospital Episode Statistics (HES) Admitted Patient Care (APC) database, an administrative database that contains information about all admissions to National Health Service (NHS) hospitals in England. 2 HES has been used by various studies to evaluate patterns of care for patients with PAD who undergo revascularisation, such as time to surgery 3 and postoperative outcomes. 4 , 5 A benefit of HES is its comprehensive coverage and its linkage with the Office for National Statistics (ONS) death registry.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, only thirty percent of interviewed patients had a secondary amputation indicating delayed presentation to medical facilities demonstrating the paucity of awareness regarding vascular diseases. This is concerning since delayed revascularization has been associated with a higher chance of postoperative amputation 29 . A cohort study of limb ischemia from Aga Khan University demonstrates that non-referral by primary physician is the main reason for late presentation 30 .…”
Section: Discussionmentioning
confidence: 99%
“…CLTI is associated with an increased risk of major limb amputation and mortality2–4 and urgent treatment is required for an optimal prognosis. However, studies examining the care pathway from first symptom to intervention have described how delays can occur at each stage of the process,5 starting with the identification and referral of patients with CLTI6 and also at the time of assessment by vascular services 7.…”
Section: Introductionmentioning
confidence: 99%